Riddle’s Court, Lawnmarket, Edinburgh: a merchant’s house fit for a king (Scottish Historical and Archaeological Internet Reports, 2023)
Riddle’s Court, a former merchant’s house situated off the Royal Mile, Lawnmarket, Edinburgh, underwent major refurbishment and transformation into the Patrick Geddes Centre for Learning from 2015 to 2017. The results from historical research, building survey and architectural watching briefs are as yet unparalleled, as no other building on the Royal Mile has received the level of historical and archaeological research carried out at Riddle’s Court.In the late 16th century much of the Royal Mile was a plethora of mainly stone and timber-framed houses. However, Riddle’s Court was an amalgam of predominantly ashlar and rubble construction with tall thatched roofs with dormer windows. Slate was a later addition in the early 18th century. The interior of the complex was furnished with several turnpike staircases of which only one now survives. During the 17th and 18th centuries Riddle’s Court was bedecked with all the fine trappings of a country mansion house and was occupied by major and minor aristocracy until the late 18th century. The status of the building was further elevated by its earlier royal connections that led to its partial remodelling for ceremonial purposes. A legacy of a lavish royal banquet in honour of King James VI of Scotland (James I of England) and his bride Queen Anne of Denmark was a painted ceiling in the so-called ‘King’s Chamber’ which commemorated their royal union. This ornate and historically significant painted beam and board ceiling was discovered in the 1960s during a period of building renovation by Edinburgh City Council. The ceiling was restored and is a focal point among a large collection of ornate plaster and painted ceilings. Subsequent removal of more modern lined ceilings during the present refurbishment led to the discovery of three more painted beam and board ceilings, and a concealed fireplace and bread oven that are rare survivors within not only the Royal Mile but elsewhere in Scotland. The presence of so much hitherto unrecorded artwork has significantly raised the importance of the Court’s North Block.